Vulneración de los derechos constitucionales y legales del trabajador, por la terminación del contrato de trabajo por acuerdo de las partes determinado en el art. 169 numeral 2 del codigo de trabajo - Arias Monar, Ximena Alexandra (2014)
In our country the private managerial sector with the purpose of not fulfilling their contractual obligations the workers in the different contract modalities, be these contracts to definite and indefinite term by means of chicaneries and deceits make sign papers in white, the same ones that are then filled with a renouncement heading to the work, taking advantage of the Art's disposition 169 numeral 2 of the Code of the Work, for agreement of the parts bringing gets the violation of their right unrenunciability, settled down in the Constitution of the Republic of the Ecuador in their Art. 326numeral 2, and in the Art.4 of the Code of the Work. This way it becomes an evident juridical insecurity to the constitutional principles recognized in International Treaties and in the effective juridical marks in labor matter, for what is necessary and indispensable and urgent to create juridical measures in the Code of the Ecuadorian Work that sanction to the employers that use the causal one second of the Art. 169 of the same normative body with the purpose of avoiding their employer obligations. Taking into account that the Art. 33 of the Fundamental Norma of the Republic establish that the work is a right and a social duty, and a right economic source of personal realization and source of the national economy, and, stiller when the Art. 326 numeral 1 and 2 of the Constitution and in the effective labor juridical mark, this is the Code of the Work in their Article 4, it keeps similarity with this numeral constitutional principle 2, and who should guide the worker's rights they are the Inspectors and Judges of Work as the Art it prepares it. 7 of the C. of the Work. It has also become habit of the private company to say goodbye to the worker inopportunely and before it presents the administrative or judicial reclamation, to require them the renouncement letter with the pretext of liquidating him the owing debits, avoiding the payment of the compensation for inopportune discharge, there are even other cases in that the date of the renouncement letter is previous to the date in that the worker ceased in the benefit of services, that is to say, he is not canceled the complete debits. Even that they force them to sign documents in white or of holding of credit like Letters of Change and Notes to the Order. For it arises it the necessity to reform the Code of the Work, establishing pecuniary sanctions in charge of the Provincial Inspection Office of the Work that sanction all abuse on the part of the employers when they request the termination of the work contract for agreement of the parts.